Steel plate and its manufacturing method

JP7606111B2Active Publication Date: 2024-12-25NIPPON STEEL CORPORATION
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022574012
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-01-07
Filing Date
2021-12-24
Publication Date
2024-12-25
Estimated Expiration
2041-12-24

AI Technical Summary

Benefits of technology

【0012】 本発明の上記態様によれば、高い強度を有するとともに、成形性、耐衝突特性、スポット溶接時の耐LME性に優れた鋼板及びその製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007606111000007
    Figure 0007606111000007
  • Figure 0007606111000001
    Figure 0007606111000001
  • Figure 0007606111000002
    Figure 0007606111000002
Patent Text Reader

Abstract

A steel sheet having a prescribed chemical composition and having a metal structure which comprises ferrite, bainite and pearlite in a combined total of 0-50 vol%, inclusive, and retained austenite in the amount of 3-20 vol%, inclusive, with the remainder constituting fresh martensite and tempered martensite, wherein: retained austenite which has an aspect ratio of 3.0 or higher constitutes at least 80%, as an area ratio, of the total retained austenite; an internal oxidation layer is present which has a thickness of at least 4.0μm from the surface of the steel sheet, a decarburized layer is present which has a thickness of 10-100μm, inclusive, from the surface of the steel sheet; and the diffusible hydrogen content contained in the steel sheet constitutes 1.00ppm or less by mass.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a steel sheet and a method for producing the same. This application claims priority based on Japanese Patent Application No. 2021-001682, filed on January 7, 2021, the contents of which are incorporated herein by reference. [Background technology]

[0002] High-strength steel sheets are used as steel sheets for automobiles in order to reduce the weight of automobiles to improve fuel efficiency, reduce carbon dioxide emissions, and ensure the safety of passengers. In recent years, in order to ensure sufficient corrosion resistance of vehicle bodies and parts, high-strength hot-dip galvannealed steel sheets as well as high-strength hot-dip galvannealed steel sheets have been used as steel sheets for automobiles in addition to high-strength hot-dip galvannealed steel sheets (see, for example, Patent Document 1).

[0003] In addition, high-strength steel sheets for automotive parts are required to have not only strength but also properties (formability) necessary for part forming, such as uniform elongation. There is a trade-off between strength and formability, but TRIP (Transformation Induced Plasticity) steel sheets, which are high-strength steel sheets that utilize the transformation-induced plasticity of retained austenite, are known as a means of achieving both.

[0004] However, when zinc-coated steel sheets (hot-dip galvanized steel sheets, electrolytic galvanized steel sheets, or alloyed hot-dip galvanized steel sheets) are spot-welded together or when cold-rolled steel sheets and zinc-coated steel sheets are spot-welded together for the assembly of vehicle bodies and / or parts, a crack called liquid metal embrittlement (LME) cracking may occur at the spot weld. LME cracking occurs when the heat generated during spot welding melts the zinc in the zinc-coated layer, the molten zinc penetrates into the grain boundaries of the steel sheet structure at the weld, and tensile stress acts on this state. Even if one of the steel sheets is a cold-rolled steel sheet that has not been zinc-coated, if the other is a zinc-coated steel sheet, LME cracking may occur when the zinc molten in the zinc-coated steel sheet comes into contact with the cold-rolled steel sheet during spot welding. LME cracking is particularly prevalent when high-strength TRIP (transformation induced plasticity) steel is spot welded. High-strength TRIP steel has higher concentrations of C, Si, and Mn than ordinary high-strength steel and contains retained austenite, giving it excellent energy absorption and press formability.

[0005] In addition, in the case of ultra-high strength steel sheets having a tensile strength of more than 980 MPa, it is necessary to solve not only the formability but also the problem of hydrogen embrittlement cracking of the steel sheet. Hydrogen embrittlement cracking is a phenomenon in which a steel member under high stress in use suddenly breaks due to hydrogen that has penetrated into the steel from the environment. This phenomenon is also called delayed fracture due to the form in which the fracture occurs. It is generally known that hydrogen embrittlement cracking of steel sheets is more likely to occur as the tensile strength of the steel sheet increases. This is thought to be because the higher the tensile strength of the steel sheet, the greater the residual stress in the steel sheet after part forming. The sensitivity to this hydrogen embrittlement cracking (delayed fracture) is called hydrogen embrittlement resistance. In the case of steel sheets for automobiles, hydrogen embrittlement cracking is particularly likely to occur in bending parts where large plastic strain is applied. Therefore, when high strength steel sheets are used for automobile parts, it is required to improve not only formability such as elongation, bendability, and hole expansion property, but also hydrogen embrittlement resistance of bending parts. The high-strength steel plates used in car bodies are easily embrittled by hydrogen in the steel, and are prone to cracking or breaking even at low stress when subjected to stress such as bending deformation.

[0006] To address such issues, for example, Patent Document 2 discloses a high-strength steel sheet that has excellent ductility and hole expandability, excellent chemical conversion treatability and plating adhesion, and good fatigue properties and hydrogen embrittlement resistance in bent portions. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] International Publication No. 2018 / 043453 [Patent Document 2] International Publication No. 2019 / 187060 Summary of the Invention [Problem to be solved by the invention]

[0008] However, in the case of automobiles, punching is performed when forming parts. As a result of investigations by the present inventors, it was found that although the high-strength steel plate of Patent Document 2 has excellent hydrogen embrittlement resistance in the bent portion, there is a concern that hydrogen embrittlement may occur at the punched end surface when punching is performed, and that there are cases in which the steel plate cannot meet the recent demand for higher crashworthiness.

[0009] As described above, conventionally, there has been no disclosure of a steel sheet that has high strength, as well as excellent formability, impact resistance (particularly impact resistance at punched portions), and LME resistance during spot welding. In view of the above, an object of the present invention is to provide a steel sheet having high strength and excellent formability (particularly uniform elongation), impact resistance (particularly punched parts), and LME resistance during spot welding, and a manufacturing method thereof. [Means for solving the problem]

[0010] The present invention has been made based on the above findings, and the gist of the present invention is as follows.

[0011] [1] A steel sheet according to one aspect of the present invention is A steel plate, Chemical composition, by mass%, is C: 0.10-0.40%, Si: 0.10-1.20%, Al: 0.30-1.50%, Mn: 1.0-4.0%, P: 0.0200% or less, S: 0.0200% or less, N: 0.0200% or less, O: 0.0200% or less, Ni: 0-1.00%, Mo: 0-0.50%, Cr: 0-2.00%, Ti: 0-0.100%, B: 0-0.0100%, Nb: 0-0.10%, V: 0-0.50%, Cu: 0-0.50%, W: 0-0.10%, Ta: 0-0.100%, Co: 0-0.50%, Mg: 0-0.050%, Ca: 0-0.0500%, Y: 0-0.050%, Zr: 0-0.050%, La: 0-0.0500%, Ce: 0-0.050%, Sn: 0-0.05%, Sb: 0-0.050%, As: 0-0.050%, and the balance being Fe and impurities; The thickness of the steel plate is measured from the surface of the plate thickness section parallel to the rolling direction to a depth of 1 / 4 of the plate thickness.In the metal structure, the volume fraction of ferrite, bainite, and pearlite is 0% or more and 50% or less in total, the volume fraction of retained austenite is 3% or more and 20% or less, and the remainder is one or two of fresh martensite and tempered martensite, and the retained austenite having an aspect ratio of 3.0 or more accounts for 80% or more of the total retained austenite in terms of area fraction, The above Surface thickness is 4.0μm or more 15.0μm or less and a decarburized layer having a thickness from the surface of the steel sheet of 10 μm or more and 100 μm or less, and an amount of diffusible hydrogen contained in the steel sheet is 1.00 ppm or less on a mass basis. the law of nature , The thickness of the internal oxidation layer is the distance from the surface to X1, where X1 is the position where the Mn concentration is 90% of the representative concentration inside the steel sheet, the decarburized layer is a region on the surface side of the steel sheet from the deepest position where the average hardness is 80% or less of the average hardness inside the steel sheet, and the amount of diffusible hydrogen is the amount of hydrogen released from the steel material from room temperature to 200°C, when measured by a temperature rise hydrogen analysis method using a gas chromatograph at a heating rate of 100°C / hour up to 300°C. . [2] In the steel sheet according to the above item [1], the surface may have a hot-dip galvanized layer. [3] In the steel sheet according to the above item [1], the surface may have a galvannealed layer. [4] A method for producing a steel sheet according to another aspect of the present invention comprises the steps of: A method for producing a steel sheet according to [1], The present invention includes a hot rolling process in which a slab having the chemical composition according to [1] is hot rolled to obtain a hot rolled steel sheet; a coiling process in which the hot rolled steel sheet is cooled at a cooling rate of 5°C / s or more and coiled at 400°C or less; a cold rolling process in which the hot rolled steel sheet after the coiling process is pickled and then cold rolled at a rolling reduction of 0.5% to 20.0% to obtain a cold rolled steel sheet; a hydrogen content reduction process in which the cold rolled steel sheet is left in the atmosphere for 1 hour or more and for t hours or more represented by the following formula (1); and an annealing process in which the cold rolled steel sheet after the hydrogen content reduction process is annealed, For rolls with a radius of 1500 mm or less A steel sheet is bent and unbent, and the cold-rolled steel sheet is heated in an atmosphere having a dew point of -20°C to 20°C and containing 0.1 to 30.0 volume% hydrogen with the remainder being nitrogen and impurities. The cold-rolled steel sheet after heating is held at a holding temperature of Ac1 to Ac3°C for 1 second to 1000 seconds. The cold-rolled steel sheet after holding is cooled to 100 to 340°C at an average cooling rate of 4°C / s or more. The cold-rolled steel sheet after cooling is reheated and held at 350°C to 480°C for 80 seconds or more. t=-2.4×T+96 (1) Here, T is the average temperature (℃) when left unattended. [5] The method for producing a steel sheet described in [4] above may further include a hot-dip galvanizing step of controlling the temperature of the cold-rolled steel sheet after the annealing step to a temperature range of (galvanizing bath temperature -40) °C to (galvanizing bath temperature +50) °C, and then immersing the cold-rolled steel sheet in a hot-dip galvanizing bath to form a hot-dip galvanizing coating on a surface of the cold-rolled steel sheet. [6] The method for producing a steel sheet according to the above item [5] may further include an alloying step of heating the hot-dip galvanized steel sheet to a temperature range of 300 to 500° C. to alloy the coating layer. Effect of the Invention

[0012] According to the above-described aspects of the present invention, it is possible to provide a steel sheet having high strength and excellent formability, impact resistance, and LME resistance during spot welding, and a manufacturing method thereof. [Brief description of the drawings]

[0013] [Figure 1] FIG. 2 is a diagram for explaining a test method for evaluating molten metal embrittlement cracking resistance (LME resistance). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, a steel sheet according to one embodiment of the present invention (steel sheet according to this embodiment) and a manufacturing method thereof will be described. The steel sheet according to this embodiment has a predetermined chemical composition described below, In metal structure, The total volume fraction of ferrite, bainite, and pearlite is 0% or more and 50% or less, The volume fraction of retained austenite is 3% or more and 20% or less, The balance is one or both of fresh martensite and tempered martensite, The retained austenite having an aspect ratio of 3.0 or more accounts for 80% or more of the total retained austenite in terms of area ratio, The steel plate has an internal oxidation layer having a thickness of 4.0 μm or more from the surface thereof, and a decarburized layer having a thickness of 10 μm or more and 100 μm or less from the surface thereof, The amount of diffusible hydrogen contained in the steel sheet is 1.00 ppm or less by mass.

[0015] <Metal structure> First, the metal structure (microstructure) of the steel plate according to this embodiment will be described. Hereinafter, the structure fraction is expressed as a volume fraction, so the unit of structure fraction "%" means volume % unless otherwise specified. In the case where the structure fraction is identified by image processing, the area fraction is regarded as the volume fraction. The metal structure of the steel plate according to this embodiment represents the metal structure at 1 / 4 of the plate thickness (1 / 4 of the plate thickness depth position from the surface in the plate thickness direction) unless otherwise specified. The reason for specifying the metal structure at 1 / 4 of the plate thickness is that in the plate thickness direction, the microstructure (constituent elements) of the steel plate may be significantly different from other parts due to decarburization and Mn segregation near the surface and near the plate thickness center, respectively, and the metal structure at 1 / 4 of the plate thickness is a representative structure of the steel plate.

[0016] [Ferrite, bainite and pearlite: 0-50% in total] Ferrite is a soft structure that is easily deformed and contributes to improving elongation, but in order to obtain a desired high strength, it is necessary to limit the volume fraction of ferrite. Bainite is a structure obtained by holding the material at 350°C or higher and 450°C or lower for a certain period of time after annealing. Bainite is softer than martensite, so it contributes to improving elongation. However, in order to obtain the desired high strength, the volume fraction must be limited, just like ferrite. Pearlite is a structure that contains hard iron carbides and serves as the starting point for the generation of voids during hole expansion. For the above reasons, in the steel plate according to this embodiment, the volume ratio of ferrite, bainite, and pearlite is set to 50% or less in total. In order to increase the strength, the total volume ratio of ferrite, bainite, and pearlite may be set to 40% or less in total. Since ferrite, bainite, and pearlite are not essential to obtain the effects of this embodiment, the lower limit is 0%.

[0017] [Residual austenite: 3~20%] The retained austenite is a structure that contributes to improving elongation (particularly uniform elongation) due to the TRIP effect. To obtain this effect, the volume fraction of the retained austenite is set to 3% or more. The volume fraction of the retained austenite is preferably 5% or more, and more preferably 7% or more. On the other hand, if the volume fraction of the retained austenite is excessive, the grain size of the retained austenite becomes large. Such retained austenite with a large grain size becomes coarse and hard martensite after deformation. In this case, it is likely to become the starting point of cracks, and the hole expandability deteriorates, which is not preferable. For this reason, the volume fraction of the retained austenite is set to 20% or less. The volume fraction of the retained austenite is preferably 18% or less, more preferably 16% or less.

[0018] In addition, in the steel sheet according to the present embodiment, as described later, the stability of the retained austenite is improved by controlling not only the volume fraction of the retained austenite but also the aspect ratio of the retained austenite. The high stability of the retained austenite can suppress the deformation-induced transformation to the fresh martensite phase, which is a hard phase, and therefore the uniform elongation is improved.

[0019] [Remainder: fresh martensite and / or tempered martensite] The balance other than the above-mentioned ferrite, bainite, pearlite, and retained austenite is one or both of fresh martensite and tempered martensite. Fresh martensite is a structure having a high dislocation density and being hard, and therefore contributes to improving tensile strength. Like fresh martensite, tempered martensite is a collection of lath-shaped crystal grains and is a structure that contributes to improving tensile strength. However, unlike fresh martensite, tempered martensite is a hard structure that contains fine iron-based carbides inside due to tempering. Tempered martensite is obtained by tempering fresh martensite, which is formed by cooling after annealing, through heat treatment or the like. Considering the volume fractions of ferrite, bainite, pearlite, and retained austenite, the total volume fraction of fresh martensite and tempered martensite is 30 to 97%.

[0020] The identification of ferrite, bainite, pearlite, retained austenite, fresh martensite, and tempered martensite in the metal structure and the calculation of their volume fractions will be described.

[0021] The volume fraction of retained austenite can be calculated by measuring the diffraction intensity using X-rays. In measurements using X-rays, a sample is cut out from a steel plate, and the surface from the surface to a depth of 1 / 4 of the plate thickness is removed by mechanical and chemical polishing. X-ray diffraction is performed on the polished surface (1 / 4 depth position) using MoKα radiation, and the structural fraction of retained austenite is calculated from the integrated intensity ratio of the diffraction peaks of (200), (211) of the bcc phase and (200), (220), and (311) of the fcc phase. The five-peak method is commonly used as the calculation method.

[0022] The volume fraction of fresh martensite is determined by the following procedure. A sample is taken so that the observation surface is the cross section of the plate thickness parallel to the rolling direction of the steel plate. The observation surface of the sample is etched with Lepera solution, and a 100μm×100μm region within 1 / 8 to 3 / 8 of the plate thickness from the surface, centered at a depth position of 1 / 4 of the plate thickness from the surface, is observed at a magnification of 3000 times using a field emission scanning electron microscope (FE-SEM), and the area ratio is determined from the obtained secondary electron image. In Lepera corrosion, fresh martensite and retained austenite are not corroded, so the area ratio of the uncorroded region is the total area ratio of fresh martensite and retained austenite. The area ratio of this uncorroded region is considered to be the total area ratio of fresh martensite and retained austenite, and the volume ratio of the retained austenite measured by the X-ray described above is subtracted from this total area ratio to calculate the volume ratio of fresh martensite.

[0023] The volume fractions of ferrite, bainite, pearlite, and tempered martensite can be determined from the secondary electron image obtained by observation using FE-SEM. The observation surface is a cross section of the plate thickness parallel to the rolling direction of the steel plate. The observation surface is polished and etched with nital, and a 100 μm x 100 μm area within 1 / 8 to 3 / 8 of the plate thickness from the surface, centered at a position 1 / 4 of the plate thickness from the surface, is observed at a magnification of 3000 times. By leaving multiple indentations around the area observed by the above-mentioned LePera corrosion, it is possible to confirm the same area as the area observed by LePera corrosion. In the observation, the inside of the grain boundary of ferrite is shown with uniform contrast. Bainite is a collection of lath-shaped crystal grains, and does not contain iron-based carbides with a long diameter of 20 nm or more inside, or contains iron-based carbides with a long diameter of 20 nm or more inside, and the carbides belong to a single variant, that is, a group of iron-based carbides elongated in the same direction. Here, the group of iron-based carbides elongated in the same direction refers to iron-based carbides whose elongation directions differ by 5° or less. Tempered martensite is a collection of lath-shaped crystal grains, and contains iron-based carbides with a long diameter of 20 nm or more inside, but the cementite in the structure has multiple variants. In addition, the region where the cementite is precipitated in a lamellar shape is pearlite. Based on these differences, each structure is identified, and the area ratio is calculated by image processing. In this embodiment, the value calculated by image processing as described above is regarded as the volume ratio.

[0024] [Proportion of retained austenite with an aspect ratio of 3.0 or more: 80% or more of the total area of ​​retained austenite] By making the retained austenite acicular, the stability of the material when strained is improved. Specifically, the retained austenite is transformed into martensite in stages from the grain boundaries, and strain is generated as a result of this transformation. As the transformation progresses, dislocations generated near the grain boundaries move through the grains to the grain boundaries on the opposite side, and dislocations accumulate. When the retained austenite is acicular, the distance from the grain boundary where the dislocations occur to the grain boundary where the dislocations accumulate is short. Therefore, a repulsive force is generated between the accumulated dislocations and the newly generated dislocations, and strain generated by the martensitic transformation is not tolerated. The above mechanism inhibits the martensitic transformation, and the stability of the retained austenite is improved. In the steel plate according to this embodiment, the retained austenite is made acicular by the method described below. However, if the shape of the retained austenite is not controlled, the retained austenite will not be acicular, and there will be variation in stability between the different retained austenite structures, resulting in poor uniform elongation. Furthermore, while hydrogen is likely to remain inside austenite, acicular austenite has a larger surface area than blocky austenite, and therefore promotes hydrogen diffusion inside the austenite during the holding process described below, thereby reducing the amount of diffusible hydrogen in the steel sheet. In this embodiment, "retained austenite having an aspect ratio of 3.0 or more" is defined as "acicular retained austenite". When the retained austenite having an aspect ratio of 3.0 or more accounts for 80% or more of the total retained austenite, uniform elongation is improved and hydrogen embrittlement resistance is improved. The retained austenite having an aspect ratio of 3.0 or more is preferably 83% or more, more preferably 85% or more of the total retained austenite. There is no particular upper limit on the proportion of retained austenite having an aspect ratio of 3.0 or more in the total retained austenite, and it is ideally 100%. The "proportion" referred to here is an area ratio, as described below. Although there is no upper limit to the aspect ratio of the retained austenite that determines the area ratio, if the aspect ratio is high, the retained austenite may become the origin of voids when transformed, which may reduce the uniform elongation. Therefore, it is preferable that the proportion of retained austenite with an aspect ratio of 3.0 to 8.0 is 80% or more.

[0025] The area ratio of retained austenite with an aspect ratio of 3.0 or more to the total retained austenite is determined by EBSD analysis using FE-SEM. Specifically, a sample is taken with the plate thickness cross section parallel to the rolling direction of the steel plate as the observation surface, the observation surface of the sample is polished, and the strain-affected layer is removed by electrolytic polishing. An EBSD analysis is performed on a 100μm×100μm area within 1 / 8 to 3 / 8 of the plate thickness from the surface, centered at a 1 / 4 depth position of the plate thickness from the surface, with a measurement step of 0.05μm. The measurement magnification is selected from 1000 to 9000 times, and may be, for example, 3000 times, the same as the observation of the SEM-backscattered electron image described above. A retained austenite map is created from the data after the measurement, and the area ratio (area of ​​retained austenite with an aspect ratio of 3.0 or more / area of ​​all retained austenite) is calculated by extracting the retained austenite with an aspect ratio of 3.0 or more.

[0026] [Internal oxide layer thickness: 4.0μm or more from the surface] The steel plate according to the present embodiment has an internal oxide layer having a thickness of 4.0 μm or more from the surface (the internal oxide layer is formed from the surface to a depth of at least 4.0 μm). The internal oxide layer is a layer in which at least a part of the grain boundary is covered with an oxide of an easily oxidizable element such as Si or Mn. By covering the grain boundary with an oxide, it is possible to suppress the penetration of molten metal into the grain boundary during welding and to suppress LME cracking during welding. If the thickness of the internal oxide layer is less than 4.0 μm, the above effect cannot be sufficiently obtained. Therefore, the thickness of the internal oxide layer is set to 4.0 μm or more. On the other hand, if the thickness of the internal oxide layer is too thick, the uniform elongation decreases, so the upper limit of the thickness of the internal oxide layer is preferably set to 15.0 μm or less. However, in the case of plated steel sheets, the surface refers to the surface of the base steel sheet (the interface between the plated layer and the base steel sheet).

[0027] The thickness of the internal oxide layer is determined by the following method. When the thickness of the steel sheet (the thickness of the base steel sheet in the case of plated steel sheet) is t, the position at t / 2 from the surface in the thickness direction is defined as the thickness center C. The thickness cross section parallel to the rolling direction of the steel sheet is used as the measurement surface, and the Mn concentration distribution is continuously measured by a high-frequency glow discharge optical emission spectrometer (GDS) over a distance of 120 μm from the surface to the thickness center C, with the surface of the steel sheet as the origin. Due to the formation of the internal oxidation layer, the solid solution Mn around the oxide becomes depleted and the Mn concentration decreases, so the Mn concentration is low in the internal oxidation layer and increases from the internal oxidation layer toward the inside of the sheet thickness, and becomes a constant concentration at a certain point. Therefore, the concentration at this constant position is defined as the representative concentration inside the steel sheet. When the Mn concentration increases from the internal oxidation layer toward the inside of the sheet thickness, the position where the Mn concentration is 90% of the representative concentration inside the steel sheet is defined as X1, and the distance from the surface to X1 is defined as the thickness of the internal oxidation layer. When analyzing by high-frequency glow discharge analysis, a known high-frequency GDS analysis method can be used. Specifically, a method is used in which the surface of the steel sheet is placed in an Ar atmosphere, a voltage is applied to generate glow plasma, and the steel sheet surface is sputtered while analyzing in the depth direction. Then, elements contained in the material (steel sheet) are identified from the element-specific emission spectrum wavelengths emitted by excited atoms in the glow plasma, and the amount of elements contained in the material is estimated from the emission intensity of the identified elements. Depth direction data can be estimated from the sputtering time. Specifically, the sputtering time can be converted to the sputtering depth by determining the relationship between the sputtering time and the sputtering depth in advance using a standard sample. Therefore, the sputtering depth converted from the sputtering time can be defined as the depth from the surface of the material. Commercially available analysis equipment can be used for high-frequency GDS analysis.

[0028] [Decarburized layer thickness: 10μm to 100μm from the surface] In order to improve the bendability after forming, it is important to soften the surface layer of the steel sheet. As a means for softening the surface layer of the steel sheet, it is considered to provide a decarburized layer on the surface layer of the steel sheet. In addition, the presence of a decarburized layer on the surface of the steel sheet provides excellent hydrogen embrittlement resistance after bending. Although the detailed mechanism by which the presence of a decarburized layer provides excellent hydrogen embrittlement resistance after bending is not clear, it is thought that decarburization reduces the amount of retained austenite in the surface layer structure, thereby reducing the amount of fresh martensite that is generated by processing-induced transformation during bending, thereby improving hydrogen embrittlement resistance. In order to obtain the above-mentioned effects, the steel plate according to this embodiment has a decarburized layer that is 10 μm or more thick from the surface of the steel plate (the decarburized layer is formed to a depth of at least 10 μm from the surface). If the thickness of the decarburized layer is less than 10 μm, the above-mentioned effects cannot be obtained sufficiently. On the other hand, if the thickness of the decarburized layer exceeds 100 μm, the strength is insufficient. Therefore, the thickness of the decarburized layer is set to 100 μm or less.

[0029] The thickness of the decarburized layer is determined by the following method. In the steel sheet according to this embodiment, the decarburized layer is defined as the region (excluding the coating layer) on the surface side of the steel sheet from the deepest position where the average hardness is 80% or less of the average hardness inside the steel sheet. In this embodiment, the average hardness inside the steel sheet and the average hardness at each position in the thickness direction of the steel sheet are obtained as follows. A sample is taken from the cross section of the steel sheet parallel to the rolling direction as the observation surface, which is polished to a mirror finish, and then chemically polished using colloidal silica to remove the processed surface layer. Using a microhardness tester, a Vickers indenter with a square pyramid shape and an apex angle of 136° is pressed into the observation surface of the obtained sample at 10 μm pitches in the thickness direction of the steel sheet, starting from a depth of 5 μm from the surface (the interface between the base steel sheet and the plating layer in the case of plated steel sheet), to a position 1 / 8 of the sheet thickness from the surface. At this time, the indentation load is set so that the Vickers indentations do not interfere with each other. For example, the indentation load is 20 gf. After that, the diagonal length of the indentations is measured using an optical microscope or a scanning electron microscope, and converted into Vickers hardness (Hv). Next, the measurement position is moved by 10 μm or more in the rolling direction, and the starting point is set at a depth of 10 μm from the surface, and the same measurement is performed up to a position of 1 / 8 of the plate thickness. Next, the measurement position is moved by 10 μm or more in the rolling direction, and the starting point is set at a depth of 5 μm from the surface, and the same measurement is performed up to a position of 1 / 8 of the plate thickness from the surface. Next, the measurement position is moved by 10 μm or more in the rolling direction, and the starting point is set at a depth of 10 μm from the outermost layer, and the same measurement is performed up to a position of 1 / 8 of the plate thickness. By repeating this, the Vickers hardness is measured at five points for each depth position. In this way, hardness measurement data is obtained at a pitch of 5 μm in the depth direction. The measurement interval is not simply set to a pitch of 5 μm in order to avoid interference between indentations. The average value of five points at the same depth position is taken as the hardness at that thickness position. The hardness profile in the depth direction is obtained by linearly interpolating between each data. In addition, the hardness of at least five points in the range from 1 / 8 thickness to 3 / 8 thickness, centered on the 1 / 4 thickness position on the same observation surface, is measured using a microhardness measuring device in the same manner as above, and the value obtained by averaging the values ​​is regarded as the average hardness inside the steel sheet. The region on the surface side of the steel plate from the deepest position where the average hardness is 80% or less of the average hardness inside the steel plate obtained as described above is defined as the decarburized layer.

[0030] In the steel sheet according to this embodiment, a decarburized layer defined as above exists in a region having a thickness of 10 to 100 μm from the surface in the sheet thickness direction. In other words, a decarburized layer having a hardness of 80% or less of the average hardness inside the steel sheet exists in the surface layer portion of the steel sheet, and the thickness of the decarburized layer is 10 to 100 μm.

[0031] [Diffusible hydrogen content in steel plate: 1.00 ppm or less] The smaller the amount of diffusible hydrogen in the steel sheet, the better the impact resistance. In the steel sheet according to the present embodiment, the amount of diffusible hydrogen in the steel sheet is set to 1.00 ppm or less by mass so that the steel sheet has excellent impact resistance even with high strength. If the amount of diffusible hydrogen exceeds 1.00 ppm, the impact resistance decreases. The amount of diffusible hydrogen is preferably 0.80 ppm or less. Hydrogen embrittlement resistance is sometimes evaluated by the critical diffusible hydrogen amount, but in the steel plate according to this embodiment, the amount of diffusible hydrogen in the steel plate is controlled with the aim of reducing the amount of hydrogen during production.

[0032] The amount of diffusible hydrogen in steel plate is measured by gas chromatographic heating hydrogen analysis (heating rate: 100°C / hour, measurement up to 300°C), and the amount of hydrogen released from the steel from room temperature to 200°C is defined as the amount of diffusible hydrogen.

[0033] Next, the reasons for limiting the chemical composition of the steel sheet according to this embodiment will be described. In the following, % in the composition means mass %.

[0034] <Chemical composition> C: 0.10-0.40% C is an element that ensures a predetermined amount of martensite (fresh martensite and tempered martensite) and improves the strength of the steel sheet. If the C content is 0.10% or more, a predetermined amount of martensite can be obtained and a desired tensile strength can be ensured. The C content is preferably 0.12% or more. On the other hand, if the C content exceeds 0.40%, the weldability and LME resistance deteriorate, and the hole expansion property deteriorates. In addition, hydrogen embrittlement resistance also deteriorates. Therefore, the C content is set to 0.40% or less. The C content is preferably 0.35% or less.

[0035] Silicon: 0.10% to 1.20% Si is a useful element for improving the strength of steel sheet by solid solution strengthening. In addition, Si suppresses the formation of cementite, and is therefore an effective element for promoting the concentration of C in austenite and forming retained austenite after annealing. In addition, Si has the effect of segregating carbon (C) on γ grain boundaries in the annealing process described below. If the Si content is less than 0.10%, it is difficult to obtain the above-mentioned effects, sufficient uniform elongation cannot be obtained, and hydrogen embrittlement resistance deteriorates, which is not preferable. Therefore, the Si content is set to 0.10% or more. The Si content is preferably 0.50% or more, more preferably 0.60% or more. On the other hand, if the Si content exceeds 1.20%, LME cracking is likely to occur during welding, and chemical conversion treatability and plating property are significantly deteriorated. Therefore, the Si content is set to 1.20% or less. The Si content is preferably 1.10% or less, and more preferably 1.00% or less.

[0036] Al: 0.30% or more, 1.50% or less Al is an element that has the effect of deoxidizing molten steel. In addition, Al suppresses the formation of cementite in the same way as Si, and is therefore an effective element for promoting the concentration of C in austenite and forming retained austenite after annealing. In the steel sheet according to the present embodiment, the Si content is set to the above-mentioned range in order to improve LME resistance, and the Al content is set to a relatively high range in order to increase the volume fraction of retained γ. Specifically, when the Al content is less than 0.30%, these effects cannot be sufficiently obtained, so the Al content is set to 0.30% or more. The Al content is preferably 0.40% or more, more preferably 0.50% or more. On the other hand, if the Al content is too high, coarse Al oxides are generated, which reduces the workability of the steel sheet. Also, if the Al content is high, the castability deteriorates. Therefore, the Al content is set to 1.50% or less. The Al content is preferably 1.40% or less, and more preferably 1.30% or less.

[0037] Mn: 1.0-4.0% Mn has the effect of improving the hardenability of steel and is an effective element for obtaining the metal structure of this embodiment. By making the Mn content 1.0% or more, a desired metal structure can be obtained. The Mn content is preferably 1.3% or more. On the other hand, if the Mn content is excessive, the effect of improving hardenability is reduced due to segregation of Mn, and the material cost increases. Therefore, the Mn content is set to 4.0% or less. The Mn content is preferably 3.5% or less.

[0038] P:0.0200% or less P is an impurity element that segregates in the center of the steel plate thickness, reducing toughness and embrittling the welded portion. If the P content exceeds 0.0200%, the welded portion strength and hole expandability are significantly reduced. Therefore, the P content is set to 0.0200% or less. The P content is preferably 0.0100% or less. The lower the P content, the better, and 0% is acceptable, but reducing the P content to less than 0.0001% in practical steel sheets significantly increases the manufacturing cost, which is economically disadvantageous, so the P content may be 0.0001% or more.

[0039] S: 0.0200% or less S is an impurity element that reduces weldability and manufacturability during casting and hot rolling. S also forms coarse MnS, which causes a decrease in hole expandability. If the S content exceeds 0.0200%, the decrease in weldability, manufacturability, and hole expandability becomes significant. Therefore, the S content is set to 0.0200% or less. The lower the S content, the better, and 0% is acceptable, but reducing the S content to less than 0.0001% in practical steel sheets significantly increases the manufacturing cost, making it economically disadvantageous, so the S content may be 0.0001% or more.

[0040] N: 0.0200% or less N is an element that forms coarse nitrides, reduces bendability and hole expandability, and causes blowholes during welding. If the N content exceeds 0.0200%, the hole expandability decreases and the occurrence of blowholes becomes significant. Therefore, the N content is set to 0.0200% or less. The lower the N content, the better, and 0% is acceptable, but reducing the N content to less than 0.0001% in practical steel sheets significantly increases the manufacturing cost, making it economically disadvantageous, so the N content may be 0.0001% or more.

[0041] O: 0.0200% or less O is an element that forms coarse oxides, reduces bendability and hole expandability, and causes blowholes during welding. If the O content exceeds 0.0200%, the hole expandability decreases and the occurrence of blowholes becomes significant. Therefore, the O content is set to 0.0200% or less. The lower the O content, the better, and 0% is acceptable, but reducing the O content to less than 0.0005% in practical steel sheets significantly increases the manufacturing cost, which is economically disadvantageous, so the O content may be 0.0005% or more.

[0042] In the chemical composition of the steel sheet according to the present embodiment, the balance excluding the above elements is basically Fe and impurities. Impurities are elements that are mixed in from the steel raw materials and / or during the steelmaking process and whose presence is permitted to the extent that they do not clearly deteriorate the properties of the steel sheet according to the present embodiment. On the other hand, the chemical composition of the steel sheet according to this embodiment may contain, in place of a portion of Fe, one or more elements selected from the group consisting of Ni: 1.00% or less, Mo: 0.50% or less, Cr: 2.00% or less, Ti: 0.100% or less, B: 0.0100% or less, Nb: 0.10% or less, V: 0.50% or less, Cu: 0.50% or less, W: 0.10% or less, Ta: 0.100% or less, Co: 0.50% or less, Mg: 0.050% or less, Ca: 0.0500% or less, Y: 0.050% or less, Zr: 0.050% or less, La: 0.0500% or less, Ce: 0.050% or less, Sn: 0.05% or less, Sb: 0.050% or less, and As: 0.050% or less, in order to improve various properties. These elements do not necessarily have to be contained, so the lower limit is 0%. Furthermore, within the above ranges, even if these elements are contained as impurities, the effects of the steel sheet according to this embodiment are not impaired.

[0043] Ni: 0 to 1.00% Ni is an element effective in improving the strength of steel sheet. The Ni content may be 0%, but in order to obtain the above effects, the Ni content is preferably 0.001% or more. The Ni content is more preferably 0.01% or more. On the other hand, if the Ni content is too high, the elongation of the steel sheet may decrease, resulting in a risk of deteriorating formability, and therefore the Ni content is set to 1.00% or less.

[0044] Mo: 0 to 0.50% Mo, like Cr, is an element that contributes to increasing the strength of steel sheets. This effect can be obtained even with a small amount of Mo. The Mo content may be 0%, but in order to obtain the above effect, the Mo content is preferably 0.01% or more. On the other hand, if the Mo content exceeds 0.50%, coarse Mo carbides are formed, which may deteriorate the cold formability of the steel sheet, so the Mo content is set to 0.50% or less.

[0045] Cr: 0~2.00% Cr is an element that improves the hardenability of steel and contributes to high strength, and is an effective element for obtaining the above-mentioned metal structure. Therefore, Cr may be contained. The Cr content may be 0%, but in order to fully obtain the above-mentioned effects, the Cr content is preferably 0.01% or more. On the other hand, if Cr is contained in excess, the above-mentioned effects become saturated and it becomes uneconomical. Therefore, the Cr content is set to 2.00% or less.

[0046] Ti: 0 to 0.100% Ti is an element that contributes to increasing the strength of steel sheets by precipitation strengthening, fine grain strengthening by inhibiting the growth of ferrite crystal grains, and / or dislocation strengthening through inhibiting recrystallization. The Ti content may be 0%, but in order to fully obtain the above effects, the Ti content is preferably 0.001% or more. In order to further increase the strength of the steel sheets, the Ti content is more preferably 0.010% or more. On the other hand, if the Ti content exceeds 0.100%, the precipitation of carbonitrides increases and formability deteriorates, so the Ti content is set to 0.100% or less.

[0047] B: 0~0.0100% B is an element that suppresses the formation of ferrite and pearlite in the metal structure during the cooling process from the austenite temperature range, and promotes the formation of low-temperature transformation structures such as bainite or martensite. B is also an element that is beneficial for increasing the strength of steel. This effect can be obtained even with a small amount. The B content may be 0%, but in order to obtain the above effect, it is preferable that the B content be 0.0001% or more. On the other hand, if the B content is too high, coarse B oxides are generated, which may become the starting points for voids during press forming, thereby reducing the formability of the steel sheet. For this reason, the B content is set to 0.0100% or less.

[0048] Nb: 0 to 0.10% Nb is an element that contributes to increasing the strength of steel sheets by precipitation strengthening, fine grain strengthening by inhibiting the growth of ferrite crystal grains, and / or dislocation strengthening through inhibiting recrystallization. The Nb content may be 0%, but in order to fully obtain the above effects, the Nb content is preferably 0.01% or more. In order to further increase the strength of steel sheets, the Nb content is more preferably 0.05% or more. On the other hand, if the Nb content exceeds 0.10%, the precipitation of carbonitrides increases and formability deteriorates. Therefore, the Nb content is set to 0.10% or less. From the viewpoint of formability, the Nb content is preferably 0.06% or less.

[0049] V: 0~0.50% V is an element that contributes to increasing the strength of steel sheets by precipitation strengthening, fine grain strengthening by inhibiting the growth of ferrite crystal grains, and / or dislocation strengthening through inhibiting recrystallization. The V content may be 0%, but in order to fully obtain the above effects, the V content is preferably 0.01% or more, and more preferably 0.02% or more. On the other hand, if the V content exceeds 0.50%, excessive carbonitrides are precipitated, deteriorating formability, so the V content is set to 0.50% or less, and preferably 0.40% or less.

[0050] Cu: 0-0.50% Cu is an element that contributes to improving the strength of steel sheet. This effect can be obtained even with a small amount. The Cu content may be 0%, but in order to obtain the above effect, the Cu content is preferably 0.01% or more. On the other hand, if the Cu content is too high, there is a risk that productivity in hot rolling will decrease due to red shortness, and therefore the Cu content is set to 0.50% or less.

[0051] W: 0~0.10% W is an element effective in improving the strength of a steel sheet. The W content may be 0%, but in order to obtain the above effects, the W content is preferably 0.01% or more. On the other hand, if the W content is too high, a large number of fine W carbides are precipitated, which may reduce the elongation due to an excessive increase in the strength of the steel sheet, and may deteriorate the cold workability of the steel sheet. For this reason, the W content is set to 0.10% or less.

[0052] Ta: 0 to 0.100% Ta is also an element effective in improving the strength of a steel sheet, similar to W. The Ta content may be 0%, but in order to obtain the above effects, the Ta content is preferably 0.001% or more. On the other hand, if the Ta content is too high, a large number of fine Ta carbides are precipitated, which increases the strength of the steel sheet excessively, reducing the elongation and the cold workability of the steel sheet. Therefore, the Ta content is set to 0.100% or less. The Ta content is preferably 0.020% or less, and more preferably 0.010% or less.

[0053] Co: 0 to 0.50% Co is an element effective in improving the strength of a steel sheet. The Co content may be 0%, but in order to obtain the above effects, the Co content is preferably 0.01% or more. On the other hand, if the Co content is too high, the elongation of the steel sheet may decrease, resulting in a risk of deteriorating formability, and therefore the Co content is set to 0.50% or less.

[0054] Magnesium: 0 to 0.050% Mg is an element that controls the morphology of sulfides and oxides and contributes to improving the bending formability of steel sheets. This effect can be obtained even with a small amount of Mg, so the Mg content may be 0%, but in order to obtain the above effect, the Mg content is preferably 0.0001% or more. On the other hand, if the Mg content is too high, there is a risk that the cold formability will deteriorate due to the formation of coarse inclusions. Therefore, the Mg content is set to 0.050% or less, and preferably 0.040% or less.

[0055] Ca: 0 to 0.0500% Like Mg, Ca is an element that can control the morphology of sulfides with a small amount. The Ca content may be 0%, but in order to obtain the above effects, the Ca content is preferably 0.0010% or more. On the other hand, if the Ca content is too high, coarse Ca oxides are generated, and these coarse Ca oxides can become the starting points for cracking during cold forming. Therefore, the Ca content is set to 0.0500% or less. The Ca content is preferably 0.0400% or less, and more preferably 0.0300% or less.

[0056] Y: 0~0.050% Y is an element that can control the morphology of sulfides with a small amount, similar to Mg and Ca. The Y content may be 0%, but in order to obtain the above effects, the Y content is preferably 0.001% or more. On the other hand, if the Y content is too high, coarse Y oxides are generated, which may deteriorate the cold formability. Therefore, the Y content is set to 0.050% or less. The Y content is preferably 0.040% or less.

[0057] Zr: 0 to 0.050% Zr is an element that can control the morphology of sulfides with a small amount, similar to Mg, Ca, and Y. The Zr content may be 0%, but in order to obtain the above effects, the Zr content is preferably 0.001% or more. On the other hand, if the Zr content is too high, coarse Zr oxides are generated, which may deteriorate the cold formability. Therefore, the Zr content is set to 0.050% or less, and preferably 0.040% or less.

[0058] La: 0 to 0.0500% La is an element that is effective in controlling the morphology of sulfides even in small amounts. The La content may be 0%, but in order to obtain the above effects, the La content is preferably 0.0010% or more. On the other hand, if the La content is too high, La oxides are generated, which may deteriorate the cold formability. Therefore, the La content is set to 0.0500% or less. The La content is preferably 0.0400% or less.

[0059] Ce: 0 to 0.050% Ce is an element that can control the morphology of sulfides with a small amount, and also contributes to improving LME resistance. In order to fully obtain the above effects, the Ce content is preferably 0.001% or more. The Ce content may be 0.002% or more, 0.003% or more, or 0.005% or more. On the other hand, if the Ce content is excessive, the steel sheet may become embrittled and the elongation of the steel sheet may decrease. Therefore, the Ce content is set to 0.050% or less. The Ce content may be 0.040% or less, 0.020% or less, or 0.010% or less.

[0060] Sn: 0 to 0.05% Sn is an element that may be contained in the steel sheet when scrap is used as the raw material of the steel sheet. Sn has an effect of improving corrosion resistance, so it may be contained, but it is an element that may cause a decrease in cold formability of the steel sheet due to embrittlement of ferrite. If the Sn content exceeds 0.05%, the adverse effects become significant, so the Sn content is set to 0.05% or less. The Sn content is preferably 0.04% or less, and may be 0%. However, reducing the Sn content to less than 0.001% leads to an excessive increase in refining costs, so the Sn content may be set to 0.001% or more.

[0061] Sb: 0 to 0.050% Like Sn, Sb is an element that may be contained in the steel sheet when scrap is used as a raw material for the steel sheet. Sb has an effect of improving corrosion resistance, so it may be contained, but it is an element that may strongly segregate at grain boundaries and cause embrittlement of grain boundaries, reduction in elongation, and reduction in cold formability. If the Sb content exceeds 0.050%, adverse effects become significant, so the Sb content is set to 0.050% or less. The Sb content is preferably 0.040% or less, and may be 0%. However, reducing the Sb content to less than 0.001% leads to an excessive increase in refining costs, so the Sb content may be set to 0.001% or more.

[0062] As: 0 to 0.050% As is an element that may be contained in a steel sheet when scrap is used as a raw material for the steel sheet, similar to Sn and Sb. As is an element that improves the hardenability of steel and may be contained, but it is an element that strongly segregates at grain boundaries and may cause a decrease in cold formability. If the As content exceeds 0.050%, the adverse effects become significant, so the As content is set to 0.050% or less. The As content is preferably 0.040% or less, and may be 0%. However, reducing the As content to less than 0.001% leads to an excessive increase in refining costs, so the As content may be set to 0.001% or more.

[0063] The chemical composition of the steel sheet according to this embodiment can be determined by the following method. The chemical composition of the above-mentioned steel sheet may be measured by a general chemical composition method. For example, it may be measured using ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry). C and S may be measured using the combustion-infrared absorption method, N may be measured using the inert gas fusion-thermal conductivity method, and O may be measured using the inert gas fusion-non-dispersive infrared absorption method. If the steel sheet has a plating layer on its surface, the plating layer may be removed by mechanical grinding before the chemical composition is analyzed.

[0064] A zinc plating layer (hot-dip galvanized layer or electrolytic zinc plating layer) may be formed on the surface (both sides or one side) of the steel sheet according to this embodiment. The hot-dip galvanized layer may be an alloyed hot-dip galvanized layer. The chemical composition of the hot-dip galvanized layer of the steel sheet according to this embodiment is not particularly limited, and may be a known plating layer. In addition, the steel sheet according to this embodiment may have another plating (e.g., aluminum plating, etc.).

[0065] When the hot-dip galvanized layer is not alloyed, the Fe content in the hot-dip galvanized layer is preferably less than 7.0 mass %. When the hot-dip galvanized layer is an alloyed hot-dip galvanized layer, the Fe content is preferably 6.0 mass% or more, and more preferably 7.0 mass% or more. The alloyed hot-dip galvanized steel sheet has better weldability than the hot-dip galvanized steel sheet.

[0066] In the steel sheet according to the present embodiment, a zinc-plated layer may be provided, and an upper plating layer may be further provided on the zinc-plated layer for the purpose of improving paintability, weldability, etc. Furthermore, the zinc-plated steel sheet may be subjected to various treatments, such as a chromate treatment, a phosphate treatment, a lubricity improvement treatment, a weldability improvement treatment, etc.

[0067] <Characteristics> [Tensile strength] In the steel sheet according to the present embodiment, the tensile strength (TS) is targeted to be 980 MPa or more, taking into consideration the contribution to improving the fuel efficiency of automobiles. The upper limit of the tensile strength is not particularly limited, but may be 1310 MPa or less from the viewpoint of formability.

[0068] [Uniform elongation] In the steel sheet according to this embodiment, the uniform elongation (u-El) is targeted to be 7.0% or more from the viewpoint of formability. The upper limit of the uniform elongation is not particularly limited.

[0069] The tensile strength and uniform elongation are measured by taking a JIS No. 5 tensile test piece described in JIS Z 2241:2011 from the steel plate in a direction perpendicular to the rolling direction and conducting a tensile test in accordance with JIS Z 2241:2011.

[0070] [Collision resistance properties] The steel plate according to this embodiment has excellent hydrogen embrittlement resistance at the punched end surface, and therefore has excellent impact resistance. For example, if a JIS No. 5 tensile test piece is punched with a semicircular hole having a diameter of 10 mm at the center of both ends and pulled along JIS Z 2241:2011, the tensile strength is TS1, and if a JIS No. 5 tensile test piece is machined with a semicircular reamed hole having a diameter of 10 mm at the center of both ends and pulled along JIS Z 2241:2011, the tensile strength is TS2, and R = TS1 / TS2, it is preferable that the value of R is 0.93 or more.

[0071] [LME resistance] The steel sheet according to this embodiment is, for example, a steel sheet that is made by welding two steel sheets, at least one of which is a zinc-plated steel sheet, at a pressure of 450 kgf (4413 kg m / s) using a servo motor pressure type single-phase AC spot welding machine (power frequency 50 Hz). 2 When plated steel sheets are spot welded while applying pressure at 0.40 V, a current of 6.5 kA, an electrode inclination angle of 3°, no upslope, a current flow time of 0.4 seconds, and a holding time after the end of current flow of 0.1 seconds, it is preferable that no cracks longer than 100 μm occur in the central region of the nugget.

[0072] Next, a method for manufacturing a steel sheet according to this embodiment will be described.

[0073] The steel plate according to this embodiment can be manufactured by a manufacturing method including the following steps. (I) a hot rolling step of hot rolling a slab having the above-mentioned chemical composition to obtain a hot rolled steel sheet; (II) a coiling step of cooling the hot-rolled steel sheet at a cooling rate of 5°C / s or more and coiling the sheet at 400°C or less; (III) a cold rolling process in which the hot-rolled steel sheet after the coiling process is pickled and then cold-rolled at a rolling reduction of 0.5% to 20.0% to obtain a cold-rolled steel sheet; (IV) a hydrogen content reduction step of leaving the cold-rolled steel sheet in the air for 1 hour or more and for t hours or more represented by the following formula (1); (V) An annealing step of annealing the cold-rolled steel sheet after the hydrogen content reduction step. t=-2.4×T+96 (1) Here, T is the average temperature (℃) when left unattended. Preferred conditions for each step are described below. For conditions not described, known conditions can be applied.

[0074] [Hot rolling process] In the hot rolling process, a slab having the above-mentioned chemical composition (similar to the chemical composition of the steel sheet according to the present embodiment) is hot rolled to obtain a hot rolled steel sheet. The slab to be subjected to hot rolling is not particularly limited as long as it has the above-mentioned chemical composition, and may be one manufactured by a conventional method. The slab may be, for example, a slab manufactured by a general method such as a continuous casting slab or a thin slab caster. In the hot rolling, rough rolling and finish rolling are performed. In the finish rolling, the slab after rough rolling is rolled by a plurality of finish rolling mills. The heating temperature and holding time of the slab before the hot rolling are not particularly limited. The thickness of the hot-rolled steel sheet obtained by hot rolling is not particularly specified, but if the thickness is less than 1.0 mm, the sheet may break during passing in the annealing process. If the thickness is thicker than 6.0 mm, the steel sheet is heavy, and even if tension is applied during passing, it may not be taut and may meander. Therefore, it is preferable that the thickness is 1.0 to 6.0 mm.

[0075] [Winding process] The steel sheet hot-rolled as described above (hot-rolled steel sheet) is cooled to a temperature of 400°C or less (coiling temperature) so that the cooling rate from the hot rolling process end temperature to the coiling temperature is always 5°C / s or more, and the steel sheet is coiled at that temperature. By setting the cooling rate (minimum cooling rate) to 5°C / s or more and the coiling temperature to 400°C or less, ferrite transformation and pearlite transformation are suppressed and a hard structure (low-temperature transformed structure) that is the source of the acicular structure is obtained. The cooling rate is preferably 10°C / s or more, more preferably 20°C / s or more. The upper limit of the cooling rate is not particularly limited, but may be 100°C / s or less from the viewpoint of manufacturability. At temperatures lower than 400°C, the cooling rate is not limited.

[0076] [Cold rolling process] In the cold rolling process, the hot-rolled steel sheet after the coiling process is pickled, and then cold-rolled at a rolling reduction of 0.5 to 20.0% to obtain a cold-rolled steel sheet. Pickling is a process for removing oxides on the surface of the hot-rolled steel sheet, and may be carried out under known conditions. Pickling may be carried out once or multiple times. Cold rolling imparts strain and increases the number of carbide precipitation sites, promoting the precipitation of iron-based carbides during the heating process of the annealing step described below. This iron-based carbide suppresses the ferrite interface movement during the heating process, allowing needle-shaped austenite to be obtained during the soaking process. To achieve this effect, the reduction rate of cold rolling is set to 0.5% or more. The reduction rate is preferably 5.0% or more. On the other hand, if the reduction rate of the cold rolling exceeds 20.0%, the ferrite interface movement is promoted during the heating process of the annealing step, and acicular austenite cannot be obtained. For this reason, the reduction rate of the cold rolling is set to 20.0% or less. The reduction rate of the cold rolling is preferably 18.0% or less.

[0077] [Hydrogen reduction process] In the hydrogen content reduction process, after the cold rolling process, the steel sheet is left in the air for t (unit: time) = [-2.4 × T + 96] or more (T is the average air temperature (℃) during the exposure) until the annealing process described below. This process can reduce the amount of hydrogen that has entered the steel sheet during the heating and pickling processes before the above-mentioned hot rolling. If t (leaving time) is less than −2.4×T+96 (hours), the amount of hydrogen cannot be reduced sufficiently. However, if T is 40° C. or higher, the exposure time shall be at least 1 hour. In other words, the exposure time shall be at least 1 hour and at least t hours.

[0078] [Annealing process] In the annealing process, the cold-rolled steel sheet after the hydrogen content reduction process is bent and unbent at 150 to 400°C, then heated in an atmosphere containing 0.1 to 30.0 volume% hydrogen and HO, with the remainder being nitrogen and impurities, with a dew point of -20 to 20°C (heating process), held at an annealing holding temperature T°C of Ac1 to Ac3°C for 1 second or more and 1000 seconds or less (soaking process), cooled to a temperature range of 350°C to 480°C at an average cooling rate of 4°C / s or more (cooling process), and held in that temperature range (350°C to 480°C) for 80 seconds or more (holding process).

[0079] (Heating process) In the heating process of the annealing step, the steel sheet is bent and unbent using rolls with a radius of 1500 mm or less while the temperature of the steel sheet is in the range of 150 to 400°C, and then heated in an atmosphere with a dew point of -20 to 20°C, containing 0.1 to 30.0 volume % hydrogen, with the remainder being nitrogen and impurities. Bending and unbending steel sheet at 150 to 400°C has two effects. First, it allows a sufficient amount of iron-based carbides to precipitate. In this case, the shape of the austenite becomes needle-like during the soaking process described below. Second, by repeatedly applying compressive deformation and tensile deformation to the steel sheet, it is possible to repeatedly change the lattice spacing inside the steel sheet, allowing hydrogen in the surface layer to be released outside the steel sheet. In addition, hydrogen present inside the steel sheet is also diffused to the surface layer side. When bending and unbending, if the temperature is less than 150°C, hydrogen does not diffuse sufficiently, resulting in an excessive diffusible hydrogen concentration in the final steel sheet. If the temperature exceeds 400°C, the dislocations imparted by bending and unbending are restored too quickly, resulting in a lack of iron-based carbides and a lack of acicular austenite. If the roll radius exceeds 1500 mm, it is difficult to efficiently introduce dislocations into the steel sheet structure by bending and unbending deformation, so the roll radius is set to 1500 mm or less. In addition, by heating in an atmosphere containing 0.1 to 30.0 volume % hydrogen, with the remainder being nitrogen and impurities, and having a dew point of -20 to 20°C, it is possible to prevent the diffusion of easily oxidizable elements to the steel sheet surface and promote internal oxidation. If the amount of hydrogen is less than 0.1% by volume, the oxide film present on the steel sheet surface cannot be sufficiently reduced, and an oxide film is formed on the steel sheet. As a result, the chemical conversion treatability and plating adhesion of the steel sheet obtained after heat treatment are reduced. Furthermore, if the amount of hydrogen exceeds 30.0% by volume, the risk of hydrogen explosion during operation increases. For this reason, the amount of hydrogen (H2 content) in the atmosphere is set to 0.1% to 30.0% by volume. Furthermore, if the dew point of the atmosphere is less than -20°C, external oxidation of Si and Mn occurs in the surface layer of the steel sheet, and internal oxidation and decarburization reactions become insufficient. In this case, LME resistance and impact resistance properties decrease. Furthermore, if the dew point is more than 20°C, an oxide film is formed on the steel sheet, which reduces the chemical conversion treatability and plating adhesion, and the decarburization reaction proceeds excessively, resulting in insufficient strength of the steel sheet obtained after annealing. The annealing furnace is roughly divided into three zones: a preheating zone, a heating zone, and a soaking zone. In this embodiment, the atmosphere in the heating zone is set to the above conditions. The atmosphere in the preheating zone and the soaking zone can also be controlled.

[0080] (Soaking process) In the soaking process, the cold-rolled steel sheet after the heating process is soaked in the temperature range of Ac1 to Ac3 for 1 to 1000 seconds. By soaking under these conditions, needle-shaped austenite is formed along the laths of the tempered martensite. The specific soaking temperature can be appropriately adjusted based on the Ac1 point (° C.) and the Ac3 point (° C.) represented by the following formula, taking into consideration the proportion of the desired metal structure. Ac1=723-10.7×Mn-16.9×Ni+29.1×Si+16.9×Cr+290×As+6.38×W (2) Ac3=910-203√C+44.7×Si-30×Mn+700×P-20×Cu-15.2×Ni-11×Cr+31.5×Mo+400×Ti+104×V+120×Al...(3) Here, C, Si, Mn, P, Cu, Ni, Cr, Mo, Ti, V and Al are the contents [mass %] of each element. If the soaking temperature is less than the Ac1 point or the soaking time is less than 1 second, austenite is not generated during soaking. Therefore, a single-phase ferrite structure is formed, and the desired metal structure is not obtained. If the soaking temperature is more than the Ac3 point, the structure during soaking becomes a single-phase austenite structure, and the form of the hard structure (low-temperature transformation structure) that is the source of the acicular structure is lost. Therefore, acicular austenite is not obtained. If the soaking time is more than 1000 seconds, productivity decreases. The soaking time in the soaking process may be set to 300 seconds or less in order to suppress coarsening of ferrite and austenite during soaking. The temperature of the steel sheet in the soaking step does not need to be constant, and may vary within the temperature range of Ac1 to Ac3 as long as the desired structure ratio can be obtained.

[0081] (cooling process) In the cooling process after the soaking process, the cold-rolled steel sheet after the soaking process is cooled to a temperature range of 100 to 340°C so that the average cooling rate is 4°C / s or more for the subsequent holding process. By cooling under such conditions, ferrite transformation during cooling can be suppressed, and the desired amount of martensite and retained austenite can be obtained in the final structure. If the average cooling rate is less than 4°C / s, ferrite transformation cannot be suppressed. If the cooling stop temperature is less than 100° C., the martensite fraction becomes high. On the other hand, if the cooling stop temperature exceeds 340° C., the ferrite, bainite, and pearlite fractions become high, making it difficult to obtain a desired structure.

[0082] (retention process) In the holding process, in order to reduce the amount of hydrogen in the steel sheet while increasing the stability of austenite, the cold-rolled steel sheet after the cooling process is reheated to a temperature range of 350 to 480°C and held at that temperature range for 80 seconds or more. If the holding time is less than 80 seconds, carbon is not sufficiently concentrated in the untransformed austenite, and hydrogen cannot be released to the outside of the steel sheet. By setting the holding time in the above temperature range to 80 seconds or more, the carbon concentration in the austenite can be increased, and a desired amount of retained austenite can be secured after final cooling. In order to stably obtain the above effect, the holding time is preferably 100 seconds or more. There is no need to limit the upper limit of the holding time, but an excessively long holding time reduces productivity, so the holding time may be 1000 seconds or less. If the holding temperature is less than 350°C, the desired amount of retained austenite cannot be obtained, and hydrogen does not diffuse sufficiently. Therefore, the holding temperature is set to 350°C or higher, preferably 380°C or higher. On the other hand, if the holding temperature exceeds 480°C, the retained austenite decomposes into ferrite and cementite, which is not preferable. Therefore, the holding temperature is set to 480°C or lower, preferably 450°C or lower.

[0083] The conditions for cooling the cold-rolled steel sheet after the holding process to room temperature are not limited, but in order to stably obtain the desired metal structure, the cold-rolled steel sheet after the holding process may be cooled to the Ms point or below at an average cooling rate of 2°C / s or more.

[0084] When reducing the amount of hydrogen in a steel sheet, as described above, control at each stage of the hydrogen amount reduction process, bending / unbending in the annealing process, and holding process is important, and a sufficient effect cannot be obtained by controlling only any one stage.

[0085] (Plating process) The method for producing a steel sheet according to the present embodiment may further include a hot-dip galvanizing step of forming a coating on the surface of the cold-rolled steel sheet during the cooling process after annealing, during the holding process, or after the holding process. Also, the method may further include an alloying step of alloying the coating layer after the hot-dip galvanizing step. The method of hot dip galvanization and the method of alloying are not particularly limited, and a conventional method can be used. For example, the method of hot dip galvanization includes a method in which cooling is stopped in the middle of the cooling process at a temperature range of (galvanizing bath temperature -40) ° C. to (galvanizing bath temperature +50) ° C., and hot dip galvanization is formed by controlling the temperature to this range and immersing in the hot dip galvanizing bath. For example, the method of alloying includes a method in which hot dip galvanization is alloyed in a temperature range of 300 to 500 ° C. EXAMPLES

[0086] The present invention will now be described more specifically with reference to examples.

[0087] A slab having the chemical composition shown in Table 1 was cast. The cast slab was heated to the temperature shown in Table 2, and then hot rolled to a thickness of 1.0 to 6.0 mm. After hot rolling, the hot-rolled steel sheet was cooled and coiled under the conditions shown in Table 2, and then cold-rolled under the conditions shown in Table 2 to obtain a cold-rolled steel sheet. These cold-rolled steel sheets were left in the air under the conditions in Table 3 to reduce the amount of hydrogen. Then, annealing was performed under the conditions shown in Tables 3 and 4. In the example where bending and unbending were performed, the bending was performed in the temperature range of 150 to 400°C using a roll with a roll diameter radius of 1100 mm. In addition, after the holding process, the steel was cooled to the Ms point or below at an average cooling rate of 2°C / s or more. Then, in some of the examples, the temperature was controlled to a range of (zinc plating bath temperature -40)°C to (zinc plating bath temperature +50)°C, and then the steel sheet was immersed in a hot dip galvanizing bath to perform plating. In some of the examples that were further plated, the steel sheet was heated to a temperature range of 300 to 500°C to alloy the plating layer. In the table, GI indicates examples where hot-dip galvanizing was performed, and GA indicates examples where alloyed hot-dip galvanizing was performed. As a result, steel sheets of example numbers 1 to 37 were obtained.

[0088] [Table 1]

[0089] [Table 2]

[0090] [Table 3]

[0091] [Table 4]

[0092] <Metal structure measurement> A test piece for SEM observation was taken from the obtained steel sheet (steel sheet after annealing or steel sheet plated after annealing), and the longitudinal section parallel to the rolling direction was polished. The metal structure was observed at 1 / 4 of the sheet thickness in the manner described above, and the area ratio of each structure (ferrite, bainite, pearlite, and the remainder (fresh martensite and / or tempered martensite)) was measured by image processing, and this was taken as the volume ratio. In addition, X-ray diffraction was performed in the manner described above to determine the volume ratio of retained austenite. The volume ratio of each structure is shown in Table 5.

[0093] Furthermore, the area ratio of retained austenite having an aspect ratio of 3.0 or more to the total retained austenite was determined for the obtained steel sheets by the EBSD analysis method using the FE-SEM in the manner described above. The results are shown in Table 5.

[0094] The thickness of the decarburized layer and the thickness of the internal oxide layer were measured for the obtained steel sheets in the manner described above. The amount of diffusible hydrogen contained in the steel sheets was also measured in the manner described above. The results are shown in Table 5.

[0095] [Table 5]

[0096] <Measurement of characteristics> In addition, the tensile strength (TS) of the obtained steel sheets, the uniform elongation (u-El) as an index of formability, the impact resistance assuming punching processing, and the LME resistance of the spot welds were evaluated using the following methods.

[0097] (Tensile strength) (Uniform elongation) JIS No. 5 tensile test pieces according to JIS Z 2241:2011 were taken from the obtained steel sheets in a direction perpendicular to the rolling direction, and tensile tests were carried out according to JIS Z 2241:2011 to measure the tensile strength and uniform elongation. A tensile strength of 980 MPa or more was considered to be acceptable. Moreover, it was determined that the formability was excellent when the uniform elongation (%) was 7.0% or more. The tensile strength measurement results are shown in Table 6.

[0098] (Collision resistance characteristics) The crashworthiness was evaluated based on the range of the R value shown in the following formula. A semicircular punched hole with a diameter of 10 mm was created in the center of both ends of a JIS No. 5 tensile test piece with a punch diameter of 10 mm and a punching clearance of 12 ± 2%, and the tensile strength when pulled along JIS Z 2241:2011 was defined as TS1. A semicircular reamed hole with a diameter of 10 mm was machined in the center of both ends of the JIS No. 5 tensile test piece, and the tensile strength when pulled along JIS Z 2241:2011 was defined as TS2, where R = TS1 / TS2. The evaluation was made according to R (=TS1 / TS2) as follows, and if it was rated A or B, it was determined that the crashworthiness was excellent. A:R=0.96~1.00 B: R = 0.93 to less than 0.96 C: R = less than 0.93

[0099] (LME resistance) Test pieces measuring 50 mm x 80 mm were taken from the obtained steel plates. In addition, a slab having the chemical composition A in Table 1 was cast, and after applying the manufacturing conditions of Example No. 1, it was immersed in a hot-dip galvanizing bath to manufacture a hot-dip galvanized steel sheet (counterpart). A test piece of 50 mm x 80 mm was taken from the manufactured steel sheet (counterpart). A steel plate serving as a counterpart material was placed on a test piece taken from each of the steel plates of Example Nos. 1 to 37, and the two steel plates were spot welded together as shown in Figure 1. Specifically, the hot-dip galvanized steel plate serving as the counterpart material was used as steel plate 1d in Figure 1, and the steel plate to be evaluated (Example Nos. 1 to 37) was used as steel plate 1e. The two steel plates were then spot welded together using a pair of electrodes 4a and 4b. The welding conditions were a pressure of 450 kgf (4413 kg m / s) using a servo motor pressure type single-phase AC spot welding machine (power frequency 50 Hz). 2 ), the current was set to 6.5 kA, the electrode inclination angle θ was set to 3°, there was no upslope, the current application time was 0.4 seconds, and the holding time after the end of current application was 0.1 seconds. After spot welding, the structure at the center of the nugget where the steel plates were joined was observed using an optical microscope at magnifications between 200 and 1000. The results of the observations were rated as "A" if no cracks occurred, "B" if cracks less than 100 μm in length were observed, and "C" if cracks 100 μm or longer were observed. A rating of A or B was deemed to indicate excellent LME resistance.

[0100] [Table 6]

[0101] As shown in Tables 1 to 6, in the examples (example numbers 1 to 16) of the present invention, the tensile strength was greater than 980 MPa, the uniform elongation was greater than 7.0%, the impact resistance index R was rated A or B, and the LME resistance (crack length after spot welding) was rated A or B.

[0102] In addition, in the case of plated steel sheets that were subjected to hot-dip galvanizing treatment or hot-dip galvanizing treatment and alloying treatment, the tensile strength was greater than 980 MPa, the uniform elongation was greater than 7.0%, the impact resistance index R was rated A or B, and the crack length after spot welding was rated A or B.

[0103] On the other hand, the comparative examples, Example Nos. 17 to 37, were out of the range of the present invention in terms of either chemical composition or structure, and were inferior in either tensile strength, uniform elongation, impact resistance, or LME resistance.

[0104] In Example No. 17, the minimum cooling rate from the hot rolling process end temperature to the coiling temperature was less than 5°C / s. Therefore, the proportion of retained austenite with an aspect ratio of 3.0 or more in the structure after annealing was small, and the amount of diffusible hydrogen contained in the steel was large. As a result, the uniform elongation and crash resistance properties were low. In sample No. 18, the coiling temperature was higher than 400°C. Therefore, the proportion of retained austenite with an aspect ratio of 3.0 or more was small, and the amount of diffusible hydrogen contained in the steel was large. As a result, the uniform elongation and crash resistance properties were low. In sample No. 19, the cold rolling reduction rate was less than 0.5% in the cold rolling process, so the proportion of retained austenite with an aspect ratio of 3.0 or more in the structure after annealing was small, and the amount of diffusible hydrogen contained in the steel was large. As a result, the uniform elongation and crash resistance properties were low. In the case of sample No. 20, the cold rolling reduction rate was more than 20.0% in the cold rolling process, so the proportion of retained austenite with an aspect ratio of 3.0 or more in the structure after annealing was small, and the amount of diffusible hydrogen contained in the steel was large. As a result, the uniform elongation and crash resistance properties were low. In the case of sample No. 21, the time during which the sample was left in the atmosphere in the hydrogen content reduction step was less than -2.4 x T + 96 (hours), so the amount of diffusible hydrogen could not be reduced sufficiently, resulting in poor crash resistance. In the case of sample No. 22, bending and unbending were not performed during the heating process of the annealing step, so the proportion of retained austenite with an aspect ratio of 3.0 or more in the structure after annealing was small, and the amount of diffusible hydrogen contained in the steel was large. As a result, the uniform elongation and crash resistance properties were low. In the case of sample No. 23, the dew point was less than -20°C during the heating process of the annealing step, so that the thickness of the internal oxide layer and the decarburized layer were not sufficient, resulting in low LME resistance. In the case of sample No. 24, the decarburized layer was too thick because the dew point exceeded 20° C. during the heating process of the annealing step. As a result, the tensile strength was low. In sample No. 25, the holding temperature in the soaking process of the annealing step was less than the Ac1 point, so the total area ratio of ferrite, bainite, and pearlite exceeded 50%, and the volume ratio of retained austenite was 0%. As a result, the tensile strength was low. In the case of sample No. 26, the holding temperature in the soaking process of the annealing step was higher than the Ac3 point, so that the volume fraction of the retained austenite was small and the proportion of the retained austenite having an aspect ratio of 3.0 or more was small. As a result, the impact resistance and uniform elongation were low. In sample No. 27, the average cooling rate in the cooling process of the annealing step was less than 4° C. / s, so the total area ratio of ferrite, bainite, and pearlite exceeded 50%, resulting in low tensile strength. In the case of sample No. 28, the holding temperature in the annealing step was less than 350° C., so that the retained austenite was not stabilized and the volume fraction of the retained austenite was small, resulting in low uniform elongation. In sample No. 29, the holding temperature in the annealing process exceeded 480° C., so the total area ratio of ferrite, bainite, and pearlite exceeded 50%, resulting in low tensile strength. In the case of sample No. 30, the holding time in the holding step of the annealing process was less than 80 seconds, so that the retained austenite was not stabilized and the volume fraction of the retained austenite was small, resulting in low uniform elongation.

[0105] In sample No. 31, the C content was less than 0.10%, so the tensile strength was low. Also, the volume fraction of retained austenite was insufficient. As a result, the uniform elongation was low. In Example No. 32, the C content exceeded 0.40%, and therefore the LME resistance was reduced. In sample No. 33, the Si content was less than 0.10%, so the volume fraction of retained austenite was insufficient, resulting in low uniform elongation. In Example No. 34, the Si content exceeded 1.20%, and therefore the LME resistance was reduced. In sample No. 35, the Al content was less than 0.30%, so the volume fraction of retained austenite was insufficient, resulting in low uniform elongation. In sample No. 36, the Mn content was less than 1.0%, and therefore the total area ratio of ferrite, bainite, and pearlite exceeded 50%, resulting in low tensile strength. In sample No. 37, the cold rolling reduction rate in the cold rolling process was less than 0.5%, and no hydrogen content reduction process was performed, so the proportion of retained austenite with an aspect ratio of 3.0 or more in the structure after annealing was small, and the amount of diffusible hydrogen contained in the steel was large. As a result, the uniform elongation and crash resistance properties were low. [Explanation of symbols]

[0106] 1d, 1e steel plate 4a, 4b electrode

Claims

1. A steel plate, The chemical composition, in mass%, is C: 0.10-0.40%, Si: 0.10-1.20%, Al: 0.30-1.50%, Mn: 1.0-4.0%, P: 0.0200% or less, S: 0.0200% or less, N: 0.0200% or less, O: 0.0200% or less, Ni: 0 to 1.00%, Mo: 0 to 0.50%, Cr: 0-2.00%, Ti: 0 to 0.100%, B: 0 to 0.0100%, Nb: 0 to 0.10%, V: 0-0.50%, Cu: 0 to 0.50%, W: 0-0.10%, Ta: 0-0.100%, Co: 0 to 0.50%, Mg: 0 to 0.050%, Ca: 0-0.0500%, Y: 0 to 0.050%, Zr: 0 to 0.050%, La: 0 to 0.0500%, Ce: 0 to 0.050%, Sn: 0 to 0.05%, Sb: 0 to 0.050%, As: 0 to 0.050%; The balance is Fe and impurities. In the metal structure at a depth position of 1 / 4 of the plate thickness in the plate thickness direction from the surface of the plate thickness cross section parallel to the rolling direction of the steel plate, The volume fraction of ferrite, bainite, and pearlite is 0% or more and 50% or less in total, The volume fraction of retained austenite is 3% or more and 20% or less, the balance being one or both of fresh martensite and tempered martensite; The retained austenite having an aspect ratio of 3.0 or more accounts for 80% or more of the total retained austenite in terms of area ratio, The steel plate has an internal oxidation layer having a thickness of 4.0 μm or more and 15.0 μm or less from the surface thereof, and a decarburized layer having a thickness of 10 μm or more and 100 μm or less from the surface thereof, The amount of diffusible hydrogen contained in the steel sheet is 1.00 ppm or less by mass, the thickness of the internal oxidation layer is a distance from the surface to a position X1 where the Mn concentration is 90% of a representative concentration inside the steel sheet, and the decarburized layer is a region on the surface side of the steel sheet relative to a deepest position where the average hardness is 80% or less of the average hardness inside the steel sheet, The amount of diffusible hydrogen is the amount of hydrogen released from the steel material from room temperature to 200° C. when measured by a temperature rise hydrogen analysis method using a gas chromatograph at a temperature rise rate of 100° C. / hour up to 300° C. steel plate.

2. The steel sheet according to claim 1 , having a hot-dip galvanized layer on the surface.

3. The steel sheet according to claim 1 , further comprising a galvannealed layer on the surface.

4. A method for manufacturing the steel sheet according to claim 1, A hot rolling process in which the slab having the chemical composition according to claim 1 is hot rolled to obtain a hot rolled steel sheet; A coiling process in which the hot-rolled steel sheet is cooled at a cooling rate of 5 ° C. / s or more and coiled at 400 ° C. or less; A cold rolling process in which the hot-rolled steel sheet after the coiling process is pickled and then cold-rolled at a rolling reduction of 0.5% to 20.0% to obtain a cold-rolled steel sheet; A hydrogen content reduction step of leaving the cold-rolled steel sheet in the air for 1 hour or more and for t hours or more represented by the following formula (1); an annealing step of annealing the cold-rolled steel sheet after the hydrogen content reduction step; having The annealing step includes: The cold-rolled steel sheet is bent and unbent at 150 to 400 ° C. using a roll having a radius of 1500 mm or less; The cold-rolled steel sheet is heated in an atmosphere having a dew point of −20° C. to 20° C., containing 0.1 to 30.0% by volume of hydrogen, with the balance being nitrogen and impurities; The cold-rolled steel sheet after heating is held at a holding temperature of Ac1 to Ac3 ° C. for 1 second to 1000 seconds, The cold-rolled steel sheet after the holding is cooled to 100 to 340 ° C. at an average cooling rate of 4 ° C. / s or more, The cold-rolled steel sheet after cooling is reheated and held at 350°C or more and 480°C or less for 80 seconds or more. Manufacturing method of steel plate. t=-2.4×T+96 (1) Here, T is the average temperature (° C.) when left standing.

5. Further, the cold-rolled steel sheet after the annealing step is controlled to a temperature range of (zinc plating bath temperature -40) ° C. to (zinc plating bath temperature +50) ° C., and then immersed in a hot-dip galvanizing bath to form a hot-dip galvanizing coating on the surface of the cold-rolled steel sheet. The method for producing the steel sheet according to claim 4.

6. Further, the method includes an alloying step of heating the hot-dip galvanized steel sheet to a temperature range of 300 to 500 ° C. to alloy the plating layer. The method for producing the steel sheet according to claim 5.

Citation Information

Patent Citations

  • High-strength plated steel sheet, as well as method for producing the same

    JP2016130357A

  • Thin steel sheet and process for producing same

    WO2018043453A1

  • Steel sheet, hot-dip zinc-coated steel sheet, and alloyed hot-dip zinc-coated steel sheet

    WO2019116531A1

  • Steel sheet and manufacturing method therefor

    WO2019187060A1

  • High-strength galvanized steel sheet having excellent electrical resistance spot weldability, and method for producing same

    WO2020130631A1